2016
DOI: 10.14296/jhrc.v2i2.2273
|View full text |Cite
|
Sign up to set email alerts
|

Readjusting the political thermostat: fuel poverty and human rights in the UK

Abstract: Fuel poverty − the inability to afford adequate warmth in the home − is a widespread problem across the UK. Cold, damp homes are detrimental to human health and contribute to thousands of 'excess winter deaths' every year. This article analyses fuel poverty from a human rights perspective -asking whether it engages human rights protections. It first discusses the definition, scale and health impacts of the problem. Second, it explores the relationship between fuel poverty and the rights contained within the Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In this sense, it is necessary to take other circumstances into consideration (political, physical, climate, etc. ), which may impact on future household vulnerability, regardless of the present socioeconomic circumstances [9,21,23,40]. Additionally, household energy vulnerability does not describe current circumstances of energy poverty, but rather the risk of exposure to this situation of any individual or household in the future.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is necessary to take other circumstances into consideration (political, physical, climate, etc. ), which may impact on future household vulnerability, regardless of the present socioeconomic circumstances [9,21,23,40]. Additionally, household energy vulnerability does not describe current circumstances of energy poverty, but rather the risk of exposure to this situation of any individual or household in the future.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Rising household expenditure on energy [2] is a variable that has contributed to a general increase in poverty, and energy poverty in particular [3]. Assuming that many authors consider energy poverty as a particular form of energy injustice suffered by the final consumers [4][5][6][7][8][9], its alleviation becomes an unavoidable responsibility for political action [10]. As a result, household energy poverty has gradually been included on political agendas, which in turn is an indicator of the degree of its impact from various perspectives [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this research is to fill this identified gap in our knowledge about the workings of an important part of the energy sector with a view to gaining a better understanding of how to achieve energy justice in this changing landscape. This has never been more important from a policy viewpoint, given the recent downgrading of the governmental pledge to eradicate fuel poverty [54].…”
Section: The Context Of the Uk Energy Marketmentioning
confidence: 99%
“…Walker and Day's (2012) pioneering contribution claims that, at its core, energy poverty is 'fundamentally a complex problem of distributive injustice' (p. 69); and suggests that this is underpinned by further injustices in recognition and policymaking procedures. Further studies have built upon this work to unpack the philosophical and moral foundations for considering energy poverty to be a form of injustice (Christman & Russell, 2016;Sovacool, Heffron, McCauley, & Goldthau, 2016).…”
Section: Energy Justicementioning
confidence: 99%